Usos sociais da leitura e da escrita em uma comunidade quilombola - Alto Jequitinhonha/MG - Patricia Barros Soares (2012)
This survey searched to examine the social usages of reading and writing among low literate people, from the analysis of meanings attributed by them to practices linked to writing language. The geographical locus we chose was Vila Nova located at the district of São Gonçalo do Rio das Pedras, no Alto Jequitinhonha/MG. From the initial contact with individuals who attended literacy classes in this community we started to be interested in analyzing the way how they and the other members acted in different activities which needed reading and writing abilities. In short how does the community deal with the abilities of reading and writing? What is the value given by low literate people to this language? In order to develop this study we adopted as a research tool the ethnographic approach using as methodological resources episode observations, field notes and interviews enabling thus, data raising, whose appreciation permitted the understanding of strategies which these individuals use in front of situations in which the usage of writing is needed. The theoretical base discusses, specially , aspects related to New Literacy Studies ( NLS ) which refer to a field study in which we can mention authors such as: Street (1984,2010) , Heath (1983 apud SOARES, 2003), Kleiman (1995) , Soares (2003,2010 ) among others, whose fundamental basis is the ethnographic perspective of literacy focusing different contexts in which individuals deal with the writing culture. The analyses resulting from the observation of the usage of writing at work and at home revealed that writing assumes plural meanings to the researched individuals , depending on the context and institutions in which they take part, sometimes ,having his usual function as in the case of an administrative register on a copybook of cash flow or sometimes as complement of religious spaces present in the rooms of some houses, sometimes having a function completely different from what is expected as in the case of decoration in some houses.